2006
DOI: 10.1111/j.1945-1474.2006.tb00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Quality Improvement to Enhance Research Readiness in Palliative Care

Abstract: Quality improvement is an essential feature of the ongoing development of palliative care programs. Little has been written, however, about using quality improvement as a strategy to introduce research concepts to staff and administrators for the purpose of enhancing research readiness in healthcare settings. This article describes such an endeavor. The authors discuss two quality improvement initiatives undertaken by a palliative care program in Canada. These two examples demonstrate how the quality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Les Canadiens proposent ainsi un véritable « contrôle de qualité » régu-lier. Ils estiment que ce soutien continu pourrait servir de catalyseur et motiver les équipes à conduire une recherche clinique [5].…”
Section: Besoin D'accompagnement Et D'intervenants Qualifiésunclassified
“…Les Canadiens proposent ainsi un véritable « contrôle de qualité » régu-lier. Ils estiment que ce soutien continu pourrait servir de catalyseur et motiver les équipes à conduire une recherche clinique [5].…”
Section: Besoin D'accompagnement Et D'intervenants Qualifiésunclassified
“…15 While active surveillance can supplement passive surveillance, it requires more time and programmatic resources, which increase the cost. 16 The WHO's COVID-19 Vaccines Safety Surveillance Manual states that each country needs ‘to determine if they have the capacity to implement active surveillance of adverse events of special interest (AESI)’ and ensure the time to implement active surveillance. 17…”
Section: Introductionmentioning
confidence: 99%
“…These resources include patients, who in the UK are registered with a single practice, and their medical records. Quality improvement studies have been suggested as a halfway house in which research concepts can be introduced to health professionals and potentially lead to enhanced research readiness [ 22 ]. There are probably many factors that contribute to whether a primary care practice is ready and willing to participate in research and make its patients and their data available to researchers.…”
Section: Introductionmentioning
confidence: 99%